Technological innovation and the complexity of imported technology: Moderating effects based on environmental regulation - Gao, Xin; Dong, Zhaoyan (Frontiers in Environmental Science, 2022)
The complexity of imported technology is an essential expression of structural optimization of import trade. Achieving high-quality import opening through import technology complexity under stricter environmental regulations and the increasing urgency of technological innovation has essential theoretical and practical significance. Given this, based on multiple database matching, this paper studies the effect of technological innovation on the complexity of imported technology and the mechanism of environmental regulation on this effect from the dimension of provincial-import source-manufacturing products (HS6). The results show that technological innovation has a positive impact on the complexity of imported technology, and environmental regulation can strengthen the positive impact of technological innovation. The moderating effect of environmental regulation is significant and differentiated at the regional and industry levels. The strengthening effects are more critical in eastern China and high pollution industries. These conclusions provide a theoretical and empirical basis for encouraging technological innovation and introducing differentiated environmental policies.